Phase and amplitude of VLF Omega signals observed simultaneously at three stations in Iceland in association with magnetospheric substorms - Araki, Takashi; Sato, Natsuo; Fujii, Ryoichi; Kikuchi, Takashi (1987)
P(論文) The phase and the field strength of 12.1kHz Omega signals propagating from Aldra, Norway have been continuously recorded at three stations (Tjornes, Isafjordur and Husafell) in Iceland using a phase locked receiver with a loop antenna parallel to the great circle path between Aldra and each stations. Sudden phase and amplitude changes associated with magnetic substorms were observed on the VLF signals, for which the phase was advanced and amplitude was increased. From the results of calculation using the full wave method with a sharp density gradient model, it is suggested that these anomalies may be interpreted to be caused by precipitating high energetic electrons. That is, the density gradient in the lower ionosphere becomes steep, and the VLF signal intensity increases due to reflection at the sharp boundary. It is also suggested from the differences of the onset time of the phase and amplitude anomaly observed at the three stations that the particle precipitation region was restricted in a small area. departmental bulletin paper